Evolution of the essence and prospects for digital economy development (Nexo Revista Científica, 2022)
The development of the digital economy in Russia lags behind the world leaders in this process. However, to become competitive in the digital space of the global economy, it is necessary to overcome this lag. This requires generalizing theoretical approaches and concepts of the digital economy in Russia and the world, tracking the evolution of views, approaches, and development prospects, analyzing the level of digitalization, digital competitiveness rating, indicators of the development of the digital economy's development and digital government. This was done in the article since the purpose of the study is to generalize theoretical approaches to the essence of the digital economy and the prospects for its growth from the point of view of evolution. Concerning findings of the study, the evolutionary stages of the development of the digital economy have been identified, SWOT analysis of the evolution of the digital economy in Russia has been carried out, a conceptual scheme for the digital transformation of business has been devised. The paper defines the essential elements of digital transformation and their relationship.